Analysis of distributed slot discontinuity in the ground plane of a microstrip line - Rassokhina, Yulia; Krizhanovski, Vladimir (Publishing House of Lviv Polytechnic National University, 2013)
This paper presentsa a method of analysis of distributed slot discontinuity in a microstrip line ground plane based on transverse resonance technique. The scattering characteristics of symmetrical and nonsymmetrical slot resonators of a complex shape have been calculated by Galerkin’s procedure and taking into account the harmonics of current density in the microstrip line and waveguide modes in the slot aperture. As a computational example the analysis of a finite cell periodic structure on the basis of П- and O-shaped slot resonators in the ground plane of a microstrip line are presented. The effectiveness and accuracy of the proposed algorithm has been verified by the comparison with measurements conducted on experimental prototypes. У роботі представлено метод аналізу розподілених шілинних неоднорідностей в уземлюючому шарі мікросмужкової лінії пересилання методом поперечного резонансу. Характеристики розсіювання симетричних та несиметричних щілинних резонаторів складної форми розраховано за методом Гальоркіна з урахуванням гармонік густини струму в мікросмужковій лінії та хвилевідних мод на апертурі щілини. Як приклад проектування представлено аналіз періодичних структур на базі П- та О-подібних щілинних резонаторів в уземлюючому шарі. Ефективність та точність запропонованого методу демонструється шляхом порівняння розрахованих характеристик із даними, отриманими в результаті вимірювань на експериментальних макетах.
Аналіз розподілених щілинних неоднорідностей в уземлюючому шарі мікрострічкової лінії пересилання
Keywords: microstrip line; slot resonator; transverse resonance technique; eigenfrequency; scattering matrix; periodic structure